Agronomic Productivity and Organic Fertilizer Rates on Growth and Yield Performance of Cabbage (Brassica oleracea var. capitata L.) in Northwestern Ethiopia - Yohannes Gelaye; Esubalew Tadele (The Scientific World Journal)
Cabbage (Brassica oleracea var. capitata L.) is a popular leafy vegetable in Ethiopia. However, the production and productivity of the crop are often constrained by several factors, such as deprived soil fertility and poor agronomic practices. Thus, a study was conducted in two locations in the East Gojjam zone of northwestern Ethiopia during the 2021/2022 cropping season to evaluate the effect of bud numbers and farmyard manure fertilizer rates on the growth and yield components of cabbage. Three numbers of cabbage buds (1, 2, and 3) and four levels of farmyard manure (0, 2.5, 5, and 7.5 tons/ha) were laid out in a 3 × 4 factorial arrangement in a randomized complete block design with three replications. Data on yield and quality were recorded and subjected to analysis of variance. The results revealed that growth, yield, and quality components were significantly influenced by the interaction effects of bud number and farmyard manure fertilizer rate. In both locations, the highest marketable (41.8 tons/ha) and total (43.1 tons/ha) yields were attained from the combined effects of 2 buds of cabbage and 5 tons of farmyard manure. The highest medium-sized heads (31.8 tons/ha) of cabbage were also recorded from the combination of 2 buds with 5 tons of farmyard manure. Moreover, the combined effects of 2 buds and 5 tons of farmyard manure showed the highest net benefit (5,679.03 US dollars) over the other treatments at the two locations. Hence, based on the results of the study, the combination of 2 buds and 5 tons of farmyard manure fertilizer can be suggested for the economical production of cabbage in northwestern Ethiopia and similar environments.